Acupuncture as multi-targeted therapy for the multifactorial disease obesity: a complex neuro-endocrine-immune interplay - Landgraaf, Raymond Guy; Bloem, Michelle Nicté; Fumagalli, Massimo; Benninga, Marc Alexander; de Lorijn, Fleur; Nieuwdorp, Max (Frontiers in Endocrinology, 2023)
The prevalence of obesity has reached pandemic dimensions. It is associated with multiple comorbidities and is becoming a clinical and public health threat. Obesity is a multifactorial disease with a complex pathophysiology and interplay of various systems. A strong interplay exists between the neuro-endocrine system, the immune system with systemic chronic low-grade inflammation, and microbiome dysbiosis that can lead to the development of obesity, which in turn can exacerbate each of these factors, hence creating a vicious cycle. The conventional treatment with lifestyle modifications such as diet, physical exercise, pharmacotherapy, and bariatric surgery does not always result in sufficient weight control thus paving the way for other strategies. As one such strategy, acupuncture is increasingly used worldwide to treat obesity. This narrative review outlines the evidence for this neuro-endocrine-immune interplay in the pathophysiology of obesity. Furthermore, the existing experimental and clinical evidence of acupuncture as a multi-targeted therapy for obesity is explained and future research perspectives are discussed.